Estudo dos polimorfismos nos genes dos TLRS em pacientes diagnósticados com Leucemia Linfoide Aguda (LLA) - Xabregas, Lilyane de Amorim (2020)
Acute lymphoblastic leukemia (ALL) is the most common hematological neoplasm and the main cause of childhood mortality. Single Nucleotide Polymorphisms (SNPs) in key molecules of the immune system, such as Toll-Like receptors, are associated with the development of various diseases, however, their role in ALL is unknown. Objective: In this study, we described the frequency of Toll-Like receptor polymorphisms in patients with acute lymphoblastic leukemia and their association with clinical prognosis. Material and Methods: A case-control study was carried out with 152 DNA samples from patients with ALL and 187 samples from individuals without the disease (control group). Genotypic and allelic discrimination was performed using the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism method (PCR-RFLP) for the TLR1 S602I (rs5743618), TLR4 A299G and I399T (rs4986790 and rs4986791), TLR5 R392S (rs5744105), TLR6 S249P (rs5743810), TLR9 -1237C/T and -1486C/T (rs5743836 and rs187084) and CD14 -159 (rs2569191) polymorphisms. Descriptive and statistical analysis was performed using Microsoft Excel 2013 and GraphPad Prism v.5.0 software. Results: The C/C genotype from -1486C/T polymorphism (TLR9) was associated with the risk of development acute lymphoblastic leukemia (TLR9: T/T + C/T vs. C/C OR = 2.0 [95% CI: 1.1 -3.5, p=0.01]; C/T vs. C/C OR = 2.2 [95% CI: 1.2–4.1, p=0.00]). In addition, the T/T genotype from - 1486 C/T (TLR9) was associated with the presence of comorbidities on diagnosis (TLR9: T/T C/T vs. C/C OR = 2.1 [95% CI: 1.1- 4.3, p=0.04]; T/T vs. C/T OR = 2.2 [95% CI: 1.0-4.7, p=0.04]). Conclusion: Our findings suggested a significant role for SNP -1486 C/T (TLR9) without the development and presence of infectious comorbidities in acute lymphoblastic leukemia